2016
DOI: 10.1007/s00203-016-1254-0
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to antifungal agents and enzymatic activity of Candida haemulonii and Cutaneotrichosporon dermatis isolated from soft corals on the Brazilian reefs

Abstract: Candida is a common fungus with the capacity to cause infections in humans. However, most studies have concentrated on clinical isolates and little is known about the identity, ecology and drug resistance of free living species/strains. Here, we isolate eight strains of Candida haemulonii and four strains of Cutaneotrichosporon dermatis from three marine cnidarian zoanthids species (Palythoa caribaeorum, Palythoa variabilis and Zoanthus sociatus) collected from Brazilian coral reefs. Strains were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
2
8
1
Order By: Relevance
“…Our results are in agreement with those reported in the literature for this fungal complex, with a commonly observed increased resistance to fluconazole [ 1 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], itraconazole, voriconazole, posaconazole and amphotericin B [ 1 , 3 , 27 , 32 , 33 , 34 ]. In general, the C. haemulonii complex exhibits in vitro susceptibility to echinocandins [ 3 , 29 , 33 , 35 , 36 , 37 ], although there are reports of resistance to this antifungal class [ 1 , 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Our results are in agreement with those reported in the literature for this fungal complex, with a commonly observed increased resistance to fluconazole [ 1 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], itraconazole, voriconazole, posaconazole and amphotericin B [ 1 , 3 , 27 , 32 , 33 , 34 ]. In general, the C. haemulonii complex exhibits in vitro susceptibility to echinocandins [ 3 , 29 , 33 , 35 , 36 , 37 ], although there are reports of resistance to this antifungal class [ 1 , 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Based on our tentative findings and literature support, we speculate that C. dermatis may achieve pathogenicity owing to its ability to produce enzymes that are damaging to human tissues, including urease, esterase, and lipase. While some studies have reported that certain C. dermatis isolates may be resistant to several common clinical antifungal agents including echinocandins and amphotericin B, we detected no evidence of antifungal resistance genes within the genome of strain NICC30027 [ 18 , 19 ]. As such, whether it is able to resist antifungal treatment warrants further study.…”
Section: Discussioncontrasting
confidence: 74%
“…Due to its ability to manufacture several essential enzymes associated with human tissues, C. dermatis has been described as an opportunistic pathogen responsible for infections of the skin, blood, and nails [ 18 ]. In addition, C. dermatis has resistance to some antifungal agents such as echinocandins and fluconazole [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…C. haemulonii First described in 1961 as Torulopsis haemulonii after having been isolated from the gut of the blue-striped grunt fish ( Haemulon sciurus ) near the U.S. Florida coast [41]. Other marine settings: Seawater near Portugal in 1962 [41] and India in 2011 [42]Soft coral ( Palythoa variabilis ) in Brazil in 2016 [43]Skin of a dolphin (species not reported) near Suriname [44]Second most common yeast from pool water of captive bottlenose dolphins ( Tursiops truncates ) in the U.S. state of Connecticut [45]Indian researchers applied C. haemulonii to giant tiger shrimp ( Penaeus monodon )—widely farmed in aquaculture—finding that its presence boosted an immunostimulatory molecule in the shrimp, conferring protection against a viral infection that causes economic losses from shrimp die-off [42]. It is unclear whether C. haemulonii has become used more broadly in aquaculture since publication of the study in 2011.…”
Section: Taxonomy and Phylogeny Of C Auris And Close Relativesmentioning
confidence: 99%